Effects of Land Use Change on Chlorophyll Concentration in Shahe River Basin of Tianmu Lake in the Past 20 Years - GONG Xiangfeng; XU Shougang; MENG Dinghua; MAO Jinqiao; GU Xiaohan; ZHU Shijie (Renmin Zhujiang)
The Shahe River Basin of Tianmu Lake provides drinking,irrigation,tourism,fishery,and other functions,which plays a crucial role in regional ecological security.In view of the actual demand and pressure of coexisting protection and development in this region,this study aims to make clear the comprehensive impact of regional eutrophication and human activities on the main water environmental factors in the reservoir area.Satellite remote sensing images and monitored chlorophyll-a concentrations in 2001,2011,and 2021 were used as basic data for research:① During the study period,the basin was in a state of moderate eutrophication.② According to remote sensing images,the land types in the Tianmu Lake area can be divided into water body,forest land,grassland,cultivated land,building land,and bare land.The cultivated land area was increased by 83% due to human activities.③ A correlation analysis was conducted between the area of each land use type and the change of chlorophyll-a concentration (the key index of water quality objective management) in the reservoir area.The results show that chlorophyll-a concentration is positively correlated with the areas of water body,forest land,building land,and cultivated land and negatively correlated with the areas of grassland and bare land.The correlation coefficients of chlorophyll-a concentration with the areas of building land and cultivated land are 0.536 and 0.773,respectively,which both influenced the water environment of the reservoir area to a certain extent.There is a close relationship between land use and water environment protection in the Shahe River Basin,which can provide important reference for the system planning and protection of the reservoir area.